2017
DOI: 10.1038/srep44184
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen results in alterations of human fetal testis development

Abstract: Among pregnant women ibuprofen is one of the most frequently used pharmaceutical compounds with up to 28% reporting use. Regardless of this, it remains unknown whether ibuprofen could act as an endocrine disruptor as reported for fellow analgesics paracetamol and aspirin. To investigate this, we exposed human fetal testes (7–17 gestational weeks (GW)) to ibuprofen using ex vivo culture and xenograft systems. Ibuprofen suppressed testosterone and Leydig cell hormone INSL3 during culture of 8–9 GW fetal testes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 69 publications
3
68
0
3
Order By: Relevance
“…This wealth of clinical experience has also suggested that ibuprofen may have other effects. There is emerging evidence that ibuprofen may in certain specific situations act as an endocrine disrupter [118,119]. The role of ibuprofen in cancer is currently being discussed in the literature, because ibuprofen offers antiproliferative benefits in some situations [120][121][122].…”
Section: Discussionmentioning
confidence: 99%
“…This wealth of clinical experience has also suggested that ibuprofen may have other effects. There is emerging evidence that ibuprofen may in certain specific situations act as an endocrine disrupter [118,119]. The role of ibuprofen in cancer is currently being discussed in the literature, because ibuprofen offers antiproliferative benefits in some situations [120][121][122].…”
Section: Discussionmentioning
confidence: 99%
“…APAP, ASA, and IBU stock solutions (500, 277, and 219 mM, respectively) (MilliporeSigma, Burlington, MA, USA) were prepared in ethanol and 10-fold diluted with PBS before oral administration between 10.5 and 13.5 dpc. For experiments with single drugs, 30 mg/kg APAP, 50 mg/kg ASA, and 15 mg/kg IBU (19,20,27,39) or 9.7% ethanol (control) were administered daily at 2 times (150 ml by gavage, 6 h apart) (n = 6 experiments with 2 pregnant females for each condition). For experiments with 2 drugs [30 mg/kg/d APAP + 50 mg/kg/d ASA, and 30 mg/kg/d APAP + 15 mg/kg/d IBU or ethanol and APAP + APAP (60 mg/kg/d) as controls], the same doses for each drug were alternately administrated every 3 h (4 times, 150 ml by gavage) (n = 4 experiments with 2 pregnant females for each condition).…”
Section: Animals and Experimental Protocolsmentioning
confidence: 99%
“…Furthermore, in a large population-based mother-child cohort, an association between simultaneous maternal use of both APAP and NSAID and shorter anogenital distance was found, whereas APAP use alone did not affect anogenital distance in the male offspring (12). Experimental in vivo/ex vivo investigations in rodents (13)(14)(15)(16) and ex vivo studies using human testicular explants (17)(18)(19)(20) showed that nontherapeutic doses of these drugs cause mild or contradictory effects on testosterone secretion. Also, when administered to adult men, IBU disrupts the hypothalamus-pituitary-gonad axis, inducing an increase in LH secretion and a decrease in testosterone production; ex vivo studies using adult testicular explants confirmed the antiandrogenic action of IBU (21).…”
mentioning
confidence: 99%
“…Concomitant reductions in prostaglandin levels, COX activity and COX gene expression have not been found in fish (Flippin et al, 2007;Lister & Van Der Kraak, 2008;Morthorst et al, 2013) and this could indicate that prostaglandin inhibitors influence the prostaglandin synthesis without affecting expression of the COX genes. That mild analgesics display a wide diversity in their responses is demonstrated in an ex vivo human foetal testis system (Ben Maamar et al, 2017). The effects on e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…14 anti-androgenic effect of mild analgesics has been demonstrated in ex vivo foetal testes of rats and humans (Kristensen et al, 2012;Ben Maamar et al, 2017), but the mechanism of action is likely to be uncoupled from the inhibition of the prostaglandin synthesis. How the inhibition of prostaglandin synthesis is related to steroids levels, steroidogenesis and reproduction remains unknown.…”
Section: Accepted Manuscriptmentioning
confidence: 99%